Perilaku Tantrum Pada Anak Usia Dini di TK ABA Sumbawa - kurniawati, luthfiyah; Utama, Abdul Alimun (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to describe the factors that cause tantrum behavior in early childhood in TK ABA Sumbawa and the efforts that teachers apply when dealing with early childhood tantrums in TK ABA Sumbawa. Tantrums happen to all children in their developmental period. Unfortunately, parents sometimes often don't realize that their child is in that period, so they use the wrong strategy, causing an impact on the child's social development to the next stage. Generally, tantrum behavior is a normal behavior that occurs in early childhood because it is a phase of the child's physical, cognitive, and emotional development. On the other hand, tantrum behavior can also be a problem in itself when it appears with a frequency, intensity, and in a relatively long time that usually occurs in children of their age. Therefore efforts in handling child tantrums have been carried out and pursued well, for example by advising children by placing the child on his lap when the child is behaving in a tantrum, teaching children to be responsible, praising and giving gifts when the child behaves well, also calm in dealing with children who are expressing tantrums, then gentle touches with strong hugs and talking calmly to children who are behaving in tantrums and providing fun activities for children who are behaving in tantrums have also been given by the school.